Difference between revisions of "Transpose of a Matrix"

From alpha
Jump to navigation Jump to search
 
Line 23: Line 23:


=== Transpose of the Transpose Matrix ===
=== Transpose of the Transpose Matrix ===
If we take the transpose of the transpose matrix, the matrix obtained is equal to the original matrix. Hence, for a matrix <math>A
If we take the transpose of the transpose matrix, the matrix obtained is equal to the original matrix.  
 
Hence, for a matrix <math>A
</math>, <math>(A^')^' = A
</math>, <math>(A^')^' = A
</math>
</math>
Line 29: Line 31:
==== Example ====
==== Example ====
If <math>A=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix}</math>  then <math>A^'=\begin{bmatrix} 3 & 6\\ 4 & 7 \\ 5 & 8 \end{bmatrix}</math>
If <math>A=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix}</math>  then <math>A^'=\begin{bmatrix} 3 & 6\\ 4 & 7 \\ 5 & 8 \end{bmatrix}</math>


<math>(A^')^'=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix} = A</math>
<math>(A^')^'=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix} = A</math>
Line 44: Line 47:
==== Example ====
==== Example ====
If <math>A=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix}</math> and <math>B=\begin{bmatrix} 1 & 2 & 3\\ 4 & 5 & 6\end{bmatrix} </math>
If <math>A=\begin{bmatrix} 3 & 4 & 5\\ 6 & 7 & 8\end{bmatrix}</math> and <math>B=\begin{bmatrix} 1 & 2 & 3\\ 4 & 5 & 6\end{bmatrix} </math>


<math>A^'=
<math>A^'=
Line 51: Line 55:
<math>A^'+B^'=\begin{bmatrix} 3+1 & 6+4 \\ 4+2 & 7+5 \\5+3 & 8+6\end{bmatrix}=
<math>A^'+B^'=\begin{bmatrix} 3+1 & 6+4 \\ 4+2 & 7+5 \\5+3 & 8+6\end{bmatrix}=
\begin{bmatrix} 4 & 10 \\ 6 & 12 \\8 & 14\end{bmatrix} </math>
\begin{bmatrix} 4 & 10 \\ 6 & 12 \\8 & 14\end{bmatrix} </math>


<math>A+B=\begin{bmatrix} 3+1 & 4+2 & 5+3\\ 6+4 & 7+5 & 8+6\end{bmatrix}=
<math>A+B=\begin{bmatrix} 3+1 & 4+2 & 5+3\\ 6+4 & 7+5 & 8+6\end{bmatrix}=
Line 59: Line 64:


=== Multiplication by Constant ===
=== Multiplication by Constant ===
If a matrix is multiplied by a constant and its transpose is taken, then the matrix obtained is equal to the transpose of the original matrix multiplied by that constant. Hence <math>(kA)^'=kA^'
If a matrix is multiplied by a constant and its transpose is taken, then the matrix obtained is equal to the transpose of the original matrix multiplied by that constant.  
 
Hence <math>(kA)^'=kA^'
</math>  where <math>k
</math>  where <math>k
</math> is a constant
</math> is a constant
Line 65: Line 72:
==== Example ====
==== Example ====
If <math>A=\begin{bmatrix} 2 & -1 & 2\\ 1 & 2 & 4\end{bmatrix}</math>
If <math>A=\begin{bmatrix} 2 & -1 & 2\\ 1 & 2 & 4\end{bmatrix}</math>


<math>A^'=\begin{bmatrix} 2 & 1\\-1 & 2\\ 2 & 4\end{bmatrix}</math>
<math>A^'=\begin{bmatrix} 2 & 1\\-1 & 2\\ 2 & 4\end{bmatrix}</math>
Line 74: Line 82:


<math>(kA)^'=\begin{bmatrix} 2k & 1k\\-1k & 2k\\ 2k & 4k\end{bmatrix}=kA^'</math>
<math>(kA)^'=\begin{bmatrix} 2k & 1k\\-1k & 2k\\ 2k & 4k\end{bmatrix}=kA^'</math>
=== Multiplication Property of Transpose ===
Transpose of the product of two matrices is equal to the product of transpose of the two matrices in reverse order.
Hence <math>(AB)^'=B^'A^'
</math>,
If <math>A=\begin{bmatrix} 3 & 4 \\ 6 & 7 \end{bmatrix}</math> and <math>B=\begin{bmatrix} 1 & 2 \\ 4 & 5 \end{bmatrix} </math>
<math>B^'=\begin{bmatrix} 1 & 4\\2 & 5\\ \end{bmatrix} </math>  <math>A^'=\begin{bmatrix} 3 & 6\\4 & 7\end{bmatrix} </math>
<math>B^'A^'=\begin{bmatrix} 1 \times 3 +4 \times 4 & 1 \times 6+4 \times 7 \\2 \times 3 + 5 \times 4 & 2 \times 6 + 5 \times 7\\\end{bmatrix}=\begin{bmatrix} 3 +16 & 6 +28 \\6 + 20& 12 + 35 \\\end{bmatrix}= \begin{bmatrix} 19 & 34 \\26& 47\\\end{bmatrix} </math>
<math>AB=\begin{bmatrix} 3 \times 1 +4 \times 4 & 3 \times 2+4 \times 5 \\6 \times 1 + 7 \times 4 & 6 \times 2 + 7 \times 5\\\end{bmatrix}=\begin{bmatrix} 3 +16 & 6 +20 \\6 + 28 & 12 + 35 \\\end{bmatrix}= \begin{bmatrix} 19 & 26 \\34& 47\\\end{bmatrix} </math>
<math>(AB)^'=\begin{bmatrix} 19 & 34 \\ 26 & 47 \end{bmatrix}=B^'A^' </math>

Latest revision as of 07:53, 5 January 2024

The transpose of a matrix is one of the most common methods used for matrix transformation in matrix concepts across linear algebra.

Definition

The transpose of a matrix is obtained by interchanging its rows into columns or columns into rows. The transpose of the matrix is denoted by using the letter in the superscript of the given matrix. For example, if is the given matrix, then the transpose of the matrix is represented by or.

Transpose of a matrix

Example

Find the transpose of

Properties of transpose of the matrices

Let us take two matrices and which have equal order. Some properties of the transpose of a matrix are given below:

Transpose of the Transpose Matrix

If we take the transpose of the transpose matrix, the matrix obtained is equal to the original matrix.

Hence, for a matrix ,

Example

If then


Addition Property of Transpose

Transpose of an addition of two matrices and obtained will be equal to the sum of the transpose of individual matrices and

Hence

Example

If and



Multiplication by Constant

If a matrix is multiplied by a constant and its transpose is taken, then the matrix obtained is equal to the transpose of the original matrix multiplied by that constant.

Hence where is a constant

Example

If



Multiplication Property of Transpose

Transpose of the product of two matrices is equal to the product of transpose of the two matrices in reverse order.

Hence ,

If and